Creating a Caregiver Benefit Finding Scale of Family Caregivers of Stroke Survivors: Development and Psychometric Evaluation - Mei, Yong-xia; Lin, Bei-lei; Zhang, Wei-hong; Wang, Shan-shan; Zhang, Zhen-xiang; Yang, Dong-bin; Cheung, Daphne Sze Ki (Frontiers in Psychiatry, 2020)
In recent years increased attention has been paid to the benefit finding of family caregivers due to the important role they play. Although some instruments measure benefit finding of caregivers, they do not comprehensively address it in specific terms to the family caregivers of stroke survivors, who require long-term, consistent care. This study is the first effort to develop a comprehensive Caregiver Benefit Finding Scale for the family caregivers of stroke survivors in Chinese cultural setting. First, 50 items were extracted from a systematic literature review and a semi-structured interview was conducted with 20 stroke family caregivers to develop the preliminary version of the scale (Version 1). Second, Delphi procedures with 20 experts were used to revise the first version and create Version 2 (37 items). Another six experts were recruited for content validation. Item content validity index (I-CVI) values ranged from 0.83 to 1.00 and the value of the scale CVI was 0.97. Third, 309 family caregivers completed the Version 2 questionnaire and the Chinese version of the Positive Aspects of Caregiving. Two weeks later, 35 family caregivers once again completed the questionnaires. An exploratory factor analysis produced four components and 26 items for Version 3 (the cumulative proportion variance was 74.14%). Subsequently, 311 family caregivers completed Version 3. A confirmatory factor analysis confirmed the structure. The goodness of fit index (GFI) = 0.921, adjusted GFI = 0.901, normal fit index = 0.951, incremental fit index = 0.990, comparative FI= 0.990, and the root mean square error of approximation= 0.02 were within the acceptable range. The criterion-related validity was equal to 0.803. The model-based internal consistency index was 0.845 and the values of the Cronbach α coefficient of the four dimensions were 0.885~0.953. The split-half reliability was 0.929 and the test-retest reliability was 0.994. These findings provide preliminary evidence of the validity and reliability of the Caregiver Benefit Finding Scale. The scale can help researchers and clinicians to achieve a more comprehensive understanding of stroke family caregivers’ positive experience. This understanding is necessary for future efforts to address issues in benefit finding by targeting the underlying mechanism and intervention.